Biomarkers for biosensors to monitor space-induced cardiovascular ageing - Rehnberg, Emil; Quaghebeur, Katrijn; Baselet, Bjorn; Rajan, Nicholas; Shazly, Tarek; Moroni, Lorenzo; Baatout, Sarah; Tabury, Kevin (Frontiers in Sensors, 2023)
Human presence in space has uncovered several health concerns related to the space environment that need to be addressed for future space missions. The hostile space environment includes radiation and microgravity that cause various pathophysiological effects. Among them are conditions related to the cardiovascular system. The cardiovascular system shows a dysfunctional and deconditioning state, similar to ageing on Earth, once exposed to the space environment. As we aim for longer space missions to the Moon, Mars, and thus into deep space, better understanding, monitoring, and development of countermeasures for these accelerated ageing processes are necessary. Biomarkers and their integration into biosensors therefore become important tools to understand the underlying mechanisms, develop countermeasures and monitor accelerated cardiovascular ageing. In this review, we will provide a brief overview of the space environment and its effects on the human cardiovascular system. We list the known potential cardiovascular ageing biomarkers relevant to space along with our current knowledge of the underlying mechanisms of cardiovascular ageing. We also explore in more details about the various biosensors used, their specifications, and how lab-on-a-chip systems are crucial to the development of these biosensors for tracking cardiovascular ageing during upcoming space missions.